Changes in the incidence, prevalence and mortality of bronchiectasis in the UK from 2004 to 2013: a population-based cohort study. Issue 1 (5th November 2015) - Quint, Jennifer K.; Millett, Elizabeth R.C.; Joshi, Miland; Navaratnam, Vidya; Thomas, Sara L.; Hurst, John R.; Smeeth, Liam; Brown, Jeremy S.
There is a paucity of data on incidence, prevalence and mortality associated with non-cystic fibrosis bronchiectasis. Using the Clinical Practice Research Datalink for participants registered between January 1, 2004 and December 31, 2013, we determined incidence, prevalence and mortality associated with bronchiectasis in the UK and investigated changes over time. The incidence and point prevalence of bronchiectasis increased yearly during the study period. Across all age groups, the incidence in women increased from 21.2 per 100 000 person-years in 2004 to 35.2 per 100 000 person-years in 2013 and in men from 18.2 per 100 000 person-years in 2004 to 26.9 per 100 000 person-years in 2013. The point prevalence in women increased from 350.5 per 100 000 in 2004 to 566.1 per 100 000 in 2013 and in men from 301.2 per 100 000 in 2004 to 485.5 per 100 000 in 2013. Comparing morality rates in women and men with bronchiectasis in England and Wales (n=11 862) with mortality rates in the general population from Office of National Statistics data showed that in women the age-adjusted mortality rate for the bronchiectasis population was 1437.7 per 100 000 and for the general population 635.9 per 100 000 (comparative mortality figure of 2.26). In men, the age-adjusted mortality rate for the bronchiectasis population was 1914.6 per 100 000 and for the general population 895.2 per 100 000 (comparative mortality figure of 2.14). Bronchiectasis is surprisingly common and is increasing in incidence and prevalence in the UK, particularly in older age groups. Bronchiectasis is associated with a markedly increased mortality. Bronchiectasis is increasing in incidence and prevalence in the UK, and is associated with an increased mortality http://ow.ly/Sh3Y9